Psychiatrist-led treatment of hepatitis C (HCV) at an opioid agonist treatment (OAT) clinic in Stockholm - enhancing the HCV treatment care cascade - M. Kåberg; P.-E. Klasa; T. Nordin (European Psychiatry, 2022)
Introduction People who inject drugs (PWID) and opioid agonist treatment (OAT) patients have an increased hepatitis C (HCV) prevalence. Studies among these populations show promising HCV treatment results, which is essential to reach the WHO goal of eliminating HCV as a major public health threat by 2030.